Nutrient accumulation and their uptake by red amaranth as influenced by different levels of N (Journal of the Bangladesh Agricultural University, 2014)
The study was conducted at the farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur during the period of November to December, 2010 to enhance the production of red amaranth (cv: BARI lal shak 1) through the determination of nutrient accumulations and their uptake by optimizing the appropriate levels of nitrogen (N) from urea. The experiment was laid out in a Randomized Complete Block Design (RCBD) comprising six treatments with four replicate each. There were altogether six levels of N viz. N0 (0 kg N ha-1), N50 (50 kg N ha-1), N75 (75 kg N ha-1), N100 (100 kg N ha-1), N125 (125 kg N ha-1) and N150 (150 kg N ha-1), respectively. P, K and S were applied from TSP, MoP and gypsum @ 23, 17 and 4 kg ha-1, respectively. Results revealed that different levels of N significantly influenced the nutrient accumulation and their uptake by red amaranth. Highest nutrient contents in most of the cases were observed when N was applied @ 150 kg ha-1 which was identical with the treatment N100 and the lowest contents were found in N0 treatment. Nutrient uptake followed similar trend like nutrient accumulation. The over result suggests that N @ 150 kg N ha-1 can be applied to boost up the production of red amaranth cv: BARI lal shak 1 under the agro-climatic conditions of the study area. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18200 J. Bangladesh Agril. Univ. 11(1): 29-32, 2013